ANALISIS PLAY WHEEL DALAM MEMPERTAHANAKAN DAYA PUTAR PADA MESIN PENCACAH PLASTIK - Abidin, Zenal; Suryadi, Dedi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
Plastic chopper machine is a machine used to crush plastics into smaller sizes, in the world of the plastic processing machine industry using kinetic energy on the fly wheel as a storage of rotational power, when the plastic chopper is working there is still a decrease in rotating power so it needs further analysis. Direct testing is carried out in the field, namely on a work system with multilevel loads on a plastic chopper, testing the endurance of a fly wheel mass that is suitable for maintaining the performance of a plastic chopper. From the test results of the play wheel mass of 55 Kg, it obtained 71 Newton's inertia, with a decrease in rotational power: 450 rpm in a period of 6 seconds, and was able to increase the turning power back in a period of 6 seconds. At a mass of 35 kg obtained 45 Newton's inertia force, a decrease in rotational power: 450 rpm in a period of 2 seconds, a rotational force: 450 rpm in a period of 2 seconds is obtained. From the test, it is obtained the influence of the mass of the ply wheel on the resistance of rotation and increase in rotation when the load is removed.